2002
DOI: 10.1074/jbc.m203179200
|View full text |Cite
|
Sign up to set email alerts
|

Adaptor Protein Shc Is an Isoform-specific Direct Activator of the Tyrosine Kinase c-Src

Abstract: The activity of c-Src protein-tyrosine kinase is upregulated under a number of receptor signaling pathways. However, the activation mechanism of c-Src under physiological conditions has remained unclear. We show here that the Shc adaptor protein is a novel direct activator of c-Src in epidermal growth factor receptor signaling in A431 human epidermoid carcinoma cells. Among the three Shc isoforms, P66 and P52, but not P46, were found to interact with and activate c-Src in vitro and in vivo. Activation of c-Src… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 49 publications
1
57
3
Order By: Relevance
“…Tyrosine residues 239 and 240 of Shc can be phosphorylated by Src (43), and Src only interacts with the two larger isoforms of Shc, but not with p46 (43,47). We only observed an effect on the small isoform.…”
Section: Discussionmentioning
confidence: 47%
“…Tyrosine residues 239 and 240 of Shc can be phosphorylated by Src (43), and Src only interacts with the two larger isoforms of Shc, but not with p46 (43,47). We only observed an effect on the small isoform.…”
Section: Discussionmentioning
confidence: 47%
“…Weng et al (43) reported that their interaction was mediated through the SH3 domain of Src and proline-rich region of Shc. A second type of interaction was described by Sato et al (39,44) who demonstrated that Src and Shc interact through the activation segment of Src and a specific 19-amino acid sequence in the N-terminal region of Shc. We addressed both possibilities using cells that expressed two different Shc mutants, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The different roles of ShcA isoforms in the intracellular networks are largely unknown. Indeed, evidence of a functional divergences between them had been reported previously (50,51). For example, the presence of the amino-terminal extension in p52Shc affects the affinity of the PTB for phosphotyrosine-containing proteins, which is approximately 10 times lower for p46Shc (50), and the region comprised between residues 29 and 45 of p52Shc, which is absent in p46Shc, is responsible for the interaction of p52 (and p66Shc) with c-Src (51).…”
Section: Discussionmentioning
confidence: 99%